2013
DOI: 10.1186/1744-8069-9-23
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C-Related but Catalytically Inactive Protein Modulates Pain Behavior in a Neuropathic Pain Model in Mice

Abstract: BackgroundAn inositol 1,4,5-trisphosphate binding protein, comprising 2 isoforms termed PRIP-1 and PRIP-2, was identified as a novel modulator for GABAA receptor trafficking. It has been reported that naive PRIP-1 knockout mice have hyperalgesic responses.FindingsTo determine the involvement of PRIP in pain sensation, a hind paw withdrawal test was performed before and after partial sciatic nerve ligation (PSNL) in PRIP-1 and PRIP-2 double knockout (DKO) mice. We found that naive DKO mice exhibited normal pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Gabarap -siRNA (1, 2) (s80666, s80665) and Kif5b -siRNA (1, 2) (s68783, s68781) were from Life Technologies (Carlsbad, CA, USA). Mouse Prip1 -siRNAs (1, 2, 3) and Prip2 -siRNAs (1, 2, 3) were described previously ( Kitayama et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gabarap -siRNA (1, 2) (s80666, s80665) and Kif5b -siRNA (1, 2) (s68783, s68781) were from Life Technologies (Carlsbad, CA, USA). Mouse Prip1 -siRNAs (1, 2, 3) and Prip2 -siRNAs (1, 2, 3) were described previously ( Kitayama et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…5d), suggesting that GABA reuptake mechanism is not involved in the prolongation of the decay of eIPSCs/eIPSPs in PRIP-DKO PCs. On the other hand, it has been reported that the deletion of PRIP-1/2 causes changes in subunit composition of GABA A Rs: PRIP-DKO mice exhibited an increased expression of GABA A Rs containing α5 subunits in spinal neurons [9] and that of GABA A Rs containing α6 subunits in cerebellar granule neurons [14]. Indeed, in GABAergic neuron-HEK cell heterosynapses, an incorporation of α6 subunits into GABA A Rs caused a slow decay of IPSCs [23].…”
Section: Differential Involvement Of Phasic and Tonic Inhibition In Tmentioning
confidence: 96%
“…It is reported that in PRIP-DKO mice, the expressions of extrasynaptic GABA A Rs containing α5 and α6 subunits are increased by 25 % in spinal neurons [9] and by 10-30 % in cerebellar granule cells [14], respectively. Therefore, we next examined whether or not tonic GABA current differs between L3 PCs in the two genotypes.…”
Section: Differential Tonic Gaba Currents Between Wt and Prip-dko Pcsmentioning
confidence: 99%
“…It is important to note that PNI also elicits activation of the BDNF-TrkB pathway in the dorsal horn neuron, which contributes to KCC2 down-regulation in these neurons and the occurrence of spinal nociception and injury-associated pain following PNI [106]. Inhibition of phospholipase C-related inactive protein (PRIP) expression induces an elevated expression of KCC2 that contributes to suppression of nociception and amelioration of neuropathic pain in PRIP-1 and PRIP-2 double knockdown mice [110].…”
Section: Kcc2 and Neuropathic Painmentioning
confidence: 99%